2021
DOI: 10.3389/fvets.2021.770202
|View full text |Cite
|
Sign up to set email alerts
|

Population Pharmacokinetics of Intravenous Amoxicillin Combined With Clavulanic Acid in Healthy and Critically Ill Dogs

Abstract: Background: Data regarding antimicrobial pharmacokinetics (PK) in critically ill dogs are lacking and likely differ from those of healthy dogs. The aim of this work is to describe a population PK model for intravenous (IV) amoxicillin–clavulanic acid (AMC) in both healthy and sick dogs and to simulate a range of clinical dosing scenarios to compute PK/PD cutoffs for both populations.Methods: This study used a prospective clinical trial in normal and critically ill dogs. Twelve client-owned dogs hospitalized in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…CMZ is one of the candidate drugs to spare carbapenems because the drug is highly stable against ESBLs ( 5 ). However, PK-PD properties of the drug, which are essential to consider optimal dosing regimens ( 23 , 24 ), are still unknown. To resolve this issue, we investigated the PK indices of CMZ in dogs and performed PK–PD analyzes using MCS.…”
Section: Discussionmentioning
confidence: 99%
“…CMZ is one of the candidate drugs to spare carbapenems because the drug is highly stable against ESBLs ( 5 ). However, PK-PD properties of the drug, which are essential to consider optimal dosing regimens ( 23 , 24 ), are still unknown. To resolve this issue, we investigated the PK indices of CMZ in dogs and performed PK–PD analyzes using MCS.…”
Section: Discussionmentioning
confidence: 99%
“…This was supported by a recent PK trial conducted in healthy and critically ill dogs, which concluded that the use of a low breakpoint precludes the selection of antimicrobials for treatable bacteria with MICs from 1 to 8 µg/mL and results in the escalation to more critical antimicrobials. 5 Beta-lactams are time-dependent antimicrobials, reaching an initial peak circulating concentration once administered, which then gradually decreases over time. 25 Once the antimicrobial concentration falls below the MIC, bacterial multiplication has been shown to resume immediately and there is an increased risk for MDR to develop.…”
Section: Discussionmentioning
confidence: 99%